The Effect of Electoral Systems on Fluid Party System in sub-Saharan Africa - Assel Bekenova (Otoritas : Jurnal Ilmu Pemerintahan, 2022)
The article, based on a literature review, examines the impact of electoral systems on the fluidity party system in sub-Saharan Africa. Most authors identify institutional and social factors influencing the change in party systems. At the same time, they use the indices Laakso and Taagepera and Rae to operationalize variable parties. However, there is a lack of research in the literature on electoral systems regarding its impact on stability or change of interparty competition patterns. This is due to, firstly, the relative novelty of the recently developed index of fluidity, and secondly, the desire of scholars to use already widely tested, established measures of measurement. We believe that, in contrast to previous studies, where the unit of analysis is the party and not the party system. The Index of Fluidity will allow us to predict how majoritarian or proportional systems and WGI scores will affect the structure or fluidity of party systems in 49 sub-Saharan African countries. The results of study indicate that the changes taking place in electoral systems have significantly affected the fluidity of party systems. The results of the study indicate that measures of WGI and ethnicity negatively affected fluidity of party systems in 49 sub-Saharan African countries. This suggests that the more unstable the party system, the more ineffective the government becomes. Whereas the results of the main hypothesis indicate a statistically significant effect of changing electoral systems on the fluidity of party systems. In other words, the more often political reforms are carried out in the electoral sphere, the higher the indicators of instability of party system, which, according to the typology of party system of Sartori, will change either radically from one-party to polarized pluralism or atomised party system or slightly from one-party to hegemonistic or predominant.